2023
DOI: 10.1021/acsanm.3c04100
|View full text |Cite
|
Sign up to set email alerts
|

Influence of A-Site Composition on the Nanostructure and Electrical Properties of APbI3 Perovskite Films: Implications for Solar Cells

Liu Yang,
Fei Zheng,
Xu Wang
et al.

Abstract: Solar cells incorporating perovskite films with a blend of A-site cations have gained significant attention due to their enhanced stability and high-power conversion efficiencies. However, the relationship between the microstructure, electrical properties of perovskite films, compositions of A-site cations, and their correlation with the charge carrier dynamics of perovskite solar cells remains unknown. In this study, we investigated the electrical properties of APbI3 perovskite films with varying A-site cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…It has been shown that the ion migration in OIHP films is significantly accelerated under a constant electric field, , and higher voltages can induce more severe ion migration. , In our experiment, since the thickness of the OIHP film is only 30–40 nm, it is possible that the ions can migrated through the film at locations with sufficient defects under a large enough bias voltage. This process could break the local perovskite lattice, resulting in grain fragmentation (Figure b-ii).…”
Section: Discussionmentioning
confidence: 73%
“…It has been shown that the ion migration in OIHP films is significantly accelerated under a constant electric field, , and higher voltages can induce more severe ion migration. , In our experiment, since the thickness of the OIHP film is only 30–40 nm, it is possible that the ions can migrated through the film at locations with sufficient defects under a large enough bias voltage. This process could break the local perovskite lattice, resulting in grain fragmentation (Figure b-ii).…”
Section: Discussionmentioning
confidence: 73%